Strategic Plan For Societal Peace And Development In Islam - Akanni, A. (Advances in Social Sciences Research Journal, 2018)
One of the good things that distinguish the modern society from the primitive one is the ability to plan for the future. This affects all aspects of human life. In today’s world, man plans for everything- his family, his cities and even the future of the world. Hence, today, one hears of family planning, development plan and strategic plan. The planning is purposely meant to enhance qualitative standard of living for all by setting specific goals to be achieved possibly within specific periods as well as step by step means of achieving those goals. It is in that spirit that the Millennium Development Goals (MDGs) as well as the Sustainable Development Goals (SDGs) both of which aimed at an effective system of global mobilization to achieve a set of imperative social priorities worldwide within specific periods were developed. Islam, which claims to address all issues on the one hand and also, claims to be a natural religion that is in tandem with human nature on the other hand amazingly also has within its structure, a strategic plan for everything! In this paper, Islam’s strategic plan for societal peace and development is examined with a view to drawing the attention of the world to it for the benefit of the human race on the one hand and on the other, to showcase the beauty of Islam as a civilized religion that envisioned man needs for all ages.